2023
DOI: 10.1158/0008-5472.c.6512529.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Cisplatin-Mediated Upregulation of APE2 Binding to MYH9 Provokes Mitochondrial Fragmentation and Acute Kidney Injury

Abstract: <div>Abstract<p>Cisplatin chemotherapy is standard care for many cancers but is toxic to the kidneys. How this toxicity occurs is uncertain. In this study, we identified apurinic/apyrimidinic endonuclease 2 (APE2) as a critical molecule upregulated in the proximal tubule cells (PTC) following cisplatin-induced nuclear DNA and mitochondrial DNA damage in cisplatin-treated C57B6J mice. The APE2 transgenic mouse phenotype recapitulated the pathophysiological features of C-AKI (acute kidney injury, AKI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To deeply investigate the mechanism by which MLLT4-AS1 regulates ATG14 protein levels, we screened MLLT4-AS1-interacting proteins and identi ed myosin-9 (MYH-9). MYH-9 (Myosin Heavy Chain 9), which encodes a conventional non-muscle myosin, has been associated with cytokinesis, cell motility and maintenance of cell shape [30][31][32]. Several studies have indicated that MYH9 favors cancer proliferation, metastasis, invasion and drug resistance [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…To deeply investigate the mechanism by which MLLT4-AS1 regulates ATG14 protein levels, we screened MLLT4-AS1-interacting proteins and identi ed myosin-9 (MYH-9). MYH-9 (Myosin Heavy Chain 9), which encodes a conventional non-muscle myosin, has been associated with cytokinesis, cell motility and maintenance of cell shape [30][31][32]. Several studies have indicated that MYH9 favors cancer proliferation, metastasis, invasion and drug resistance [33,34].…”
Section: Discussionmentioning
confidence: 99%